Dinamika novičarskega diskurza populizma in ekstremizma - Pušnik, Maruša (Dve domovini, 2017)
The article examines the characteristics of extreme populist news discourses and their right-wing policies in the case of xenophobic discussions of refugees and Islam. It analyzes news articles about refugees from two weeklies, Reporter and Demokracija, which are self-described as right-wing-oriented political weeklies, in order to reveal the implementation of their populist policy. This policy is based on authoritarianism, militarism, nativism and ethnic nationalism, the culturalisation of economic policy and on the techniques of arousing disgust and hatred instead of compassion, and it is rearticulated in relation to refugees - Muslim immigrants - who are presented as a threat to "our" freedoms. The article notes that Islamophobia and extreme populist discourses, which are spreading via the news discourse, replace the biological with the cultural, but also refugees with Muslim immigrants, which gives us a new form of cultural racism.
Keywords: Begunci; Ekstremizem; Extremism; Journalistic discourse; Nacionalizem; Nationalism; Novinarski diskurz; Refugees